A multicenter mixed-methods study on the effects of intermittent fasting in patients with immune thrombocytopenia receiving thrombopoietin receptor agonists - Mohamed A. Yassin; Mohamed A. Yassin; Muna AlRasheed; Taghreed Al-Eisa; Noura Alhashim; Fiasal Alsayegh; Tarek E. Abouzeid; Mohamed Abd El Fattah; Maryam Alfili; Neveen Shalaby; Neveen Shalaby; Abdullah Alotaibi; et al. (Frontiers in Nutrition)
IntroductionIn recent years, significant advances have been made in the treatment of immune thrombocytopenia (ITP) with the development of thrombopoietin receptor agonists (TPO-RAs). TPO-RAs are often used following the failure of prior therapies or when bleeding episodes persist despite glucocorticoid use. In Muslim countries, where religious observance includes 16/8 intermittent fasting, the timing of medication administration may be affected. This study is the first to evaluate the impact of Ramadan fasting on patients receiving different TPO-RAs.MethodsA multicenter mixed-design study was performed in which Muslim patients who fasted during Ramadan while receiving TPO-RAs were interviewed between 2015 and 2023. Patient responses before, during, and after Ramadan were evaluated retrospectively. The bleeding tendency was assessed as (1) no bleeding, (2) minor cutaneous/mucosal bleeding, or (3) severe bleeding that involves major organs.ResultsThe present study included 100 patients from three Muslim countries, including Qatar, Kuwait, and Saudi Arabia, across four tertiary centers. A complete response was observed in 63% of patients on ROM, 46% on ELT and 37% on AVA. For AVA, the mean platelet (PLT) count before Ramadan was estimated at [146.11 ± 111.76], while during Ramadan, it dropped to [131.7 ± 107.6]. For patients on ELT, the mean PLT count before Ramadan was estimated at [120.02 ± 59.7], while during Ramadan, it dropped to [100.8 ± 68.16] (p = 0.016). For patients on ROM, the mean platelet count before Ramadan was estimated at [122.68 ± 80.57], while during Ramadan, it was [130.94 ± 84.96]. Only 3% (3 patients on ELT) experienced bleeding episodes.ConclusionThis study supports the feasibility of Ramadan fasting for ITP patients receiving TPO-RAs. Further studies with a larger sample size are recommended to investigate the impact of other types of fasting on the efficacy and safety of TPO-RAs.